Modelling the Hafnium–Neodymium Evolution of Early Earth: A Study from West Greenland. (5th December 2018) - Gardiner, Nicholas J; Johnson, Tim E; Kirkland, Christopher L; Szilas, Kristoffer
Abstract: The processes of partial melting and the segregation and migration of melt underpin the differentiation of the lithosphere. The Sm–Nd and Lu–Hf isotopic systems, which are sensitive to these processes, behave similarly during mantle–crust differentiation, leading to isotopically coupled primary (basaltic) and continental (tonalite–trondhjemite–granodiorite, TTG) crustal compositions that define a linear terrestrial fractionation array in εNd vs εHf space. However, Eoarchaean basalts and TTGs from West Greenland do not sit on this trend and are isotopically decoupled, which may reflect their extraction from a mantle with a non-chondritic composition. We explore the effects of source composition vs fractionation on the production and evolution of early Archaean crust. We use phase equilibria and trace element modelling to characterize the Hf–Nd isotopic evolution of a chain of melting from anhydrous mantle through hydrated basalt to TTG. We show that ∼20% decompression melting of anhydrous mantle with a superchondritic Sm/Nd but chondritic Lu/Hf composition at a mantle potential temperature appropriate to the early Archaean produces basaltic melts with an isotopic composition similar to those measured in Eoarchaean tholeiitic basalts from Isua, West Greenland. In turn, 5–30% melting of hydrated basalt produces TTG melts with Hf–Nd isotopic compositions similar to those measured in Eoarchaean TTGs from the Itsaq Gneiss Complex, West Greenland. Thus, we chart a chain of melting from an isotopically decoupled Hf–Nd mantle composition to isotopically decoupled mafic and felsic crust. Our modelling defines an overall Hf–Nd isotopic fractionation trend that is parallel to, but offset from, that defined by modern rocks with coupled compositions. Primitive mantle contamination by 5% recycled continental crust (TTG) requires a higher degree of mantle melting (30%) to produce basaltic melt with a Hf–Nd composition similar to the Isua basalts. A mantle composition with greater than 5% crustal contamination is more enriched than the Isua basalts, placing an upper limit on the amount of crustal contaminant. A non-chondritic mantle source composition in the early Archaean likely imposed a first order control on the subsequent production of crust with decoupled Hf–Nd compositions.